2007
DOI: 10.1128/jvi.01242-07
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 and CXCR3 Are Dispensable for Liver Infiltration, but CCR5 Protects against Virus-Induced T-Cell-Mediated Hepatic Steatosis

Abstract: CCR5 and CXCR3 are important molecules in regulating the migration of activated lymphocytes. Thus, the majority of tissue-infiltrating T cells found in the context of autoimmune conditions and viral infections express CCR5 and CXCR3, and the principal chemokine ligands are expressed within inflamed tissues. Accordingly, intervention studies have pointed to nonredundant roles of these receptors in models of allograft rejection, viral infection, and autoimmunity. In spite of this, considerable controversy exists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
1
9
1
Order By: Relevance
“…Nevertheless, CCR5‐deficiency resulted in hyper‐inflammatory responses in our murine model of viral infection similar to that reported by other groups 4, 7, 33, 34. It is not known whether humans with naturally occurring CCR5 null mutations have increased susceptibility to influenza as has been seen for other viral pathogens 40, 41, and this warrants further investigation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, CCR5‐deficiency resulted in hyper‐inflammatory responses in our murine model of viral infection similar to that reported by other groups 4, 7, 33, 34. It is not known whether humans with naturally occurring CCR5 null mutations have increased susceptibility to influenza as has been seen for other viral pathogens 40, 41, and this warrants further investigation.…”
Section: Discussionsupporting
confidence: 83%
“…However, two independent groups have reported spontaneous production of IFN‐γ by CCR5 −/− and CXCR3 −/− /CCR5 −/− CD8 T cells 13, 32. Also, antigen‐specific clonal expansion of T cells and T‐cell‐mediated immunopathology was augmented in CCR5 −/− mice infected with lymphocytic choriomeningitis virus 33, 34. Yurchenko et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that CXCR3 and its ligands contributed to the development of necroinflammatory liver damage and progression towards fibrosis in chronic HCV patients [1928] and other virus-infected liver diseases [29, 30], which implied the possible involvement of chemokine (IP-10 and MIG)-chemokine receptor (CXCR3) interactions in the pathogenesis of PBC [31, 32]. Although studies in human PBC have shown the presence of CXCR3 + T cells in liver tissues, the contribution of CXCR3 to the recruitment of T cells to these inflamed tissues was not well established.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Besides HIV infection, CCR5 has been involved in a large number of disorders as described by epidemiological, clinical or basic studies. So, there are good evidences that linked CCR5 to liver diseases (e.g., hepatocellular carcinoma and liver steatosis), [3][4][5][6] autoimmune disorders (e.g., rheumatoid arthritis), [7] pulmonary diseases (e.g., pulmonary arterial hypertension and sarcoidosis), [8,9] organ rejection (e.g., stem cell transplant), [10] malignancies (e.g., colorectal cancer), [11] and vascular diseases (e.g., endothelial dysfunction and atherogenesis). [12,13] Therefore, we wonder if CCR5 antagonist could be an attractive therapeutic option to prevent and/or treat different inflammatory and/or malignant diseases.…”
Section: Off-label Use Of Maraviroc In Clinical Practicementioning
confidence: 99%